2015
DOI: 10.1371/journal.pone.0124566
|View full text |Cite
|
Sign up to set email alerts
|

Mild Cognitive Impairment: Vascular Risk Factors in Community Elderly in Four Cities of Hebei Province, China

Abstract: BackgroundEvidence has demonstrated that vascular risk factors (VRFs) contribute to mild cognitive impairment (MCI) in the elderly population. Because of the race and different diagnosis standard, there is still no definitive conclusions.ObjectiveTo estimate the VRFs and potential protective factors for MCI in elderly population living in the community in North China.MethodsA total of 3136 participants entered the study. They were screened for hypertension, coronary heart disease (CHD), and cerebrovascular dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 43 publications
1
27
2
Order By: Relevance
“…Heart disease was not a significant factor. The study in China demonstrated that stroke and DM but not hypertension and coronary heart disease were related risk factors of MCI [10]. Another Chinese study found that DM was shown to be a risk factor of MCI progressing to AD.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…Heart disease was not a significant factor. The study in China demonstrated that stroke and DM but not hypertension and coronary heart disease were related risk factors of MCI [10]. Another Chinese study found that DM was shown to be a risk factor of MCI progressing to AD.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…However, the MoCA-B (Thai version) was already developed for screening MCI in illiterate and low education populations [18]. A study in China found that the prevalence of MCI was 20%, and it was significantly higher in people who did not exercise [10]. The study worldwide of the prevalence of MCI in diverse geographical and ethnocultural regions which analyzed data from 11 international cohort studies which included USA, Europe, Asia and Australia found that the estimation of MCI prevalence was 5.0-36.7%.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12] Cognitive dysfunction has an adverse effect on self-care behavior, while poor glycemic control has also been shown to be a risk factor for cognitive dysfunction. 13,14 Middle-aged patients with T2DM were found to exhibit a certain degree of cognitive dysfunction. 15,16 However, the impact of cognitive dysfunction on the selfcare behavior of young and middle-aged adult patients is not well characterized.…”
Section: Introductionmentioning
confidence: 99%